The effect of irrigation and nitrogen fertilization on the soybean seed yield, with a correlation to the protein and oil concentration - Galić Subašić, Daria (Array, 2020)
The paper presents the result of a triennial field experiment (2013‒15), aiming to determine the influence of irrigation, nitrogen fertilization, and cultivars, as well as their interactions on the yield and chemical properties of the soybean seeds. Four soybean cultivars (Lucija, Vita, Ika and Tena) of different maturity groups were investigate as a sub‐subplot factor (C). The main plot factor (A - irrigation) resulted in a statistically very significant (P≤0.01) seed yield in all three years, and it was found out by an analysis of variance. The subplot factor (B - nitrogen fertilization) had an impact on the grain yield depending on the research year, while sub‐subplot factor (C-cultivar) significantly affected all examined traits. The factor interactions and their significance varied by the research years. The seed yield achieved in 2013 (3883 kg ha-1) indicated a great importance of all factors’ interaction. The correlations between a seed yield and a protein and oil concentration were determined during the research.